2019
DOI: 10.1038/s41419-019-1896-3
|View full text |Cite
|
Sign up to set email alerts
|

LINC01232 exerts oncogenic activities in pancreatic adenocarcinoma via regulation of TM9SF2

Abstract: Pancreatic adenocarcinoma (PAAD), one of the most prevailing malignant tumors in digestive system, is identified as one of the main culprits of cancer-associated mortality. Despite long intergenic non-protein coding RNA 1232 (LINC01232) is found to be upregulated in TCGA PAAD tissues and associated with poor prognosis, the potential of LINC01232 in PAAD progression still needs more explorations. In this study, LINC01232 was chosen to be the research object in PAAD cellular processes. Functionally, loss-of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…RNA‐binding proteins (RBPs) are known to exert their functions via interplaying with RNAs to affect stability, expression, function, and cellular location in tumors 9,10 . For instance, LINC01232 exerts promotive properties in pancreatic adenocarcinoma upon TM9SF2 by recruiting EIF4A3 11 . LIN28B‐AS1 activates LIN28B by binding to IGF2BP1 in lung adenocarcinoma 12 .…”
Section: Introductionmentioning
confidence: 99%
“…RNA‐binding proteins (RBPs) are known to exert their functions via interplaying with RNAs to affect stability, expression, function, and cellular location in tumors 9,10 . For instance, LINC01232 exerts promotive properties in pancreatic adenocarcinoma upon TM9SF2 by recruiting EIF4A3 11 . LIN28B‐AS1 activates LIN28B by binding to IGF2BP1 in lung adenocarcinoma 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed LncRNAs can recruit RBPs to regulate the downstream genes by changing the stability of their mRNAs. [32][33][34][35] Through dual screening of target prediction and RNA pull down assay, we identified EIF4A3, a vital exon junction complex component that participates in the development of secondary structure of mRNA in the 5′UTR region and promotes the initiation of translation of proteins. 36,37 We confirmed CASC11 could specially bind to EIF4A3, and the binding site was located in fragment of nucleotides 437-654 of CASC11.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01232 expression is upregulated in pancreatic adenocarcinoma, and a high level of expression is associated with a poor clinical outcome ( 26 ). LINC01232 functions as an oncogenic lncRNA in pancreatic adenocarcinoma and regulates cell proliferation, apoptosis, migration, invasion and the epithelial-mesenchymal transition ( 26 ). However, the expression and roles of LINC01232 in ESCC have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Long intergenic non-coding RNA LINC01232 has been identified as a critical regulator of pancreatic adenocarcinoma oncogenesis ( 26 ). However, the involvement of LINC01232 in ESCC has not yet been thoroughly elucidated.…”
Section: Introductionmentioning
confidence: 99%